Students’ Perspective of Google Classroom (GCR) Online Learning during Covid-19 Pandemic - Novalia Rani Jayatri; Risnawati Risnawati; Ferri Susanto (Jadila: Journal of Development and Innovation in Language and Literature Education, 2021)
This research aimed to find out the implementation of Google Classroom (GCR) in Online Learning during Covid-19 Pandemic for the second year students of SMAN 08 Kota Bengkulu and to find out the Students’ Perspective of Google Classroom (GCR) in Online Learning during Covid-19 Pandemic at SMAN 08 Kota Bengkulu. There were 30 students who participated in this research gathered by using purposive sampling. The research method applied in this current study was a qualitative method. The data were collected through observation, interviews and documentation. To analyze the data, the researcher applied the theory from Miles and Huberman (1994). The result of the first research question showed that Google Classroom was used frequently by the teacher and students to conduct online learning. The result of the second research question demonstrated that only 48,84% of the students were satisfied with the use of Google Classroom. The students were not satisfied the most with the students’ indicator of satisfaction, which reached 75%. However, 92,7% of them gave positive feedback towards the instruction delivery. Overall, this result suggested that Google Classroom did not received positive feedback from the majority of the students, with some exception of instruction delivery. The researcher recommended the teacher at SMAN 08 Kota Bengkulu to provide more creative way in online teaching, so students have the opportunity to learn more effectively.